Integrated Glycosylation Patterns of Glycoproteins and DNA Methylation Landscapes in Mammalian Oogenesis and Preimplantation Embryo Development - Wang, Jian; Tian, Geng G.; Li, Xiaoyong; Sun, Yangyang; Cheng, Li; Li, Yanfei; Shen, Yue; Chen, Xuejin; Tang, Wenwei; Tao, Shengce; Wu, Ji (Frontiers in Cell and Developmental Biology, 2020)
Glycosylation is one of the most fundamental post-translational modifications. However, the glycosylation patterns of glycoproteins have not been analyzed in mammalian preimplantation embryos, because of technical difficulties and scarcity of the required materials. Using high-throughput lectin microarrays of low-input cells and electrochemical techniques, an integration analysis of the DNA methylation and glycosylation landscapes of mammal oogenesis and preimplantation embryo development was performed. Highly noticeable changes occurred in the level of protein glycosylation during these events. Further analysis identified several stage-specific lectins including LEL, MNA-M, and MAL I. It was later confirmed that LEL was involved in mammalian oogenesis and preimplantation embryogenesis, and might be a marker of FGSC differentiation. Modified nanocomposite polyaniline/AuNPs were characterized by electron microscopy and modification on bare gold electrodes using layer-by-layer assembly technology. These nanoparticles were further subjected to accuracy measurements by analyzing the protein level of ten-eleven translocation protein (TET), which is an important enzyme in DNA demethylation that is regulated by O-glycosylation. Subsequent results showed that the variations in the glycosylation patterns of glycoproteins were opposite to those of the TET levels. Moreover, analysis of correlation between the changes in glyco-gene expression and female germline stem cell glycosylation profiles indicated that glycosylation was related to DNA methylation. Subsequent integration analysis showed that the trend in the variations of glycosylation patterns of glycoproteins was similar to that of DNA methylation and opposite to that of the TET protein levels during female germ cell and preimplantation embryo development. Our findings provide insight into the complex molecular mechanisms that regulate human embryo development, and a foundation for further elucidation of early embryonic development and informed reproductive medicine.